Two's Company, Three's a Crowd? Triads in Cooperative-Competitive Networks - Madhavan, Ravindranath; Gnyawalị, Devi R.; He, Jinyu (Academy of Management Journal, 2004)
Triadic structure is an important, but neglected, aspect of interfirm networks. We developed the constructs clustering and countering as potential drivers of triadic structure and combined them with the recently developed p* network model to demonstrate the value and feasibility of triadic analysis. Exploratory analysis of data from the global steel industry revealed firms' tendency to form transitive triads, in which three firms all have direct ties with each other, especially within blocks defined by geography or technology.